2021
DOI: 10.1016/j.stemcr.2021.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Human motor units in microfluidic devices are impaired by FUS mutations and improved by HDAC6 inhibition

Abstract: Neuromuscular junctions (NMJs) ensure communication between motor neurons (MNs) and muscle; however, in MN disorders, such as amyotrophic lateral sclerosis (ALS), NMJs degenerate resulting in muscle atrophy. The aim of this study was to establish a versatile and reproducible in vitro model of a human motor unit to investigate the effects of ALS-causing mutations. Therefore, we generated a co-culture of human induced pluripotent stem cell (iPSC)-derived MNs and human primary mesoangioblast-derived myotubes in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 61 publications
2
84
0
Order By: Relevance
“…In neurodegenerative diseases such as ALS, microfluidic models have shown promise in the investigation of the effectiveness of drugs delivered to the distal axons located outside the CNS as opposed to delivery to the soma, which is more difficult to target with treatment in vivo ( Marshall and Farah, 2021 ). Microfluidic models using ALS patient specific iPSC derived MNs expressing mutant FUS demonstrated a reduction in neurite outgrowth and the number of total NMJs and showed that histone deacetylase 6 inhibition could rescue outgrowth impairments and improve NMJ formation ( Stoklund Dittlau et al, 2021 ). Another study using a 3D microfluidic approach demonstrated that motor units using iPSC derived motor neurons from a patient with sporadic ALS produced weaker muscle cell contractions compared to healthy donor derived controls, and treatment with mTOR pathway inhibitors increased muscle contractile force and improved motor neuron survival in the ALS model ( Osaki et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In neurodegenerative diseases such as ALS, microfluidic models have shown promise in the investigation of the effectiveness of drugs delivered to the distal axons located outside the CNS as opposed to delivery to the soma, which is more difficult to target with treatment in vivo ( Marshall and Farah, 2021 ). Microfluidic models using ALS patient specific iPSC derived MNs expressing mutant FUS demonstrated a reduction in neurite outgrowth and the number of total NMJs and showed that histone deacetylase 6 inhibition could rescue outgrowth impairments and improve NMJ formation ( Stoklund Dittlau et al, 2021 ). Another study using a 3D microfluidic approach demonstrated that motor units using iPSC derived motor neurons from a patient with sporadic ALS produced weaker muscle cell contractions compared to healthy donor derived controls, and treatment with mTOR pathway inhibitors increased muscle contractile force and improved motor neuron survival in the ALS model ( Osaki et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, human iPSC-derived co-cultures of astrocytes and motor neurons were recently used in a study showing that astrocytes exhibit non-cell autonomous effects on motor neurons in an in vitro ALS model ( Zhao et al, 2020 ). For studies on neuromuscular disease, co-cultures of iPSC-derived motor neurons with skeletal muscle cells (such as those derived from C2C12 mouse myoblasts, primary human-derived myoblasts, or differentiated from hiPSCs, with varying degrees of difficulty and availability) to simulate a simplified version of the neuromuscular system present in vivo , and allowing for assays of NMJ function ( Demestre et al, 2015 ; Picchiarelli et al, 2019 ; Lin et al, 2020 ; Yoshioka et al, 2020 ; Stoklund Dittlau et al, 2021 ). Furthermore, organoid culture systems allow for the differentiation of multiple cell types to form a miniature version and experimentally approachable model of the tissue of interest ( Vieira de Sa et al, 2021 ).…”
Section: Enhancing Cell Maturity and Exploring Cell Biological Mechanismsmentioning
confidence: 99%
“…Moreover, the knowledge acquired from these publications should lay the groundwork for the development of diseased models employing human patient‐specific cells to be used for the investigation of the pathological mechanisms underlying NMJ damage and neurodegenerative diseases. [ 18–20 ] In particular, the study of the NMJ contribution in muscular dystrophies progression is still poorly explored as compared to other neuromuscular disorders and would widely benefit from the microfluidics approach. The NMJ pathological derangement has been characterized in the Duchenne Muscular Dystrophy (DMD) and pointed out numerous differences in the structure, function, and gene expression between the healthy and pathologic condition.…”
Section: Introductionmentioning
confidence: 99%